CONFLICTS, POLITICAL INSTABILITY, AND ILLEGAL TRADE OF ANTIQUITIES IN DISTRICT DIR LOWER KHYBER PAKHTUNKHWA: AN ANALYSIS OF PUBLIC PERCEPTION - Nangyalay Khan; Dr. Faisal Khan; Dr. Syed Zafar Ullah Bakhshali; Bakht Ullah; Prof. Dr. Arab Naz (PalArch's Journal of Archaeology of Egypt / Egyptology, 2023)
Conflicts, Political Instability, and Illegal Trade of Antiquities have posed significant challenges to the protection and preservation of archaeological sites. Archaeological sites hold immense historical and cultural significance, however, during periods of conflict, political instability, unrest, and non-state armed groups' actions, the archaeological sites as well as antiquities illegal trade remain dominant. District Dir Lower, rich in cultural heritage, has been adversely affected by conflicts, leading to the destruction and damage of valuable historical landmarks and artifacts. The absence of stable governance and inadequate resource allocation for preservation worsens the problem. Additionally, this also has contributed to illegal trade of antiquities due to the region's strategic location and insufficient law enforcement during time of conflict. This research thus explores the perception of community about the impact of conflicts on archaeological sites and the role of law in mitigating destruction, and the measures for restoration of the archeological sites during post-conflict era. It further analyzes the effectiveness of international and national legal frameworks and identifies perceptions of illegal trade and looting of the sites. The study aims to contribute to strategies that protect and restore archaeological heritage, ensuring its preservation for future generations.